An approach to remove homoepitaxially grown GaN layers by cleavage from the substrate surface. (13th March 2020) - Gandrothula, Srinivas; Kamikawa, Takeshi; Araki, Masahiro; Cohen, Daniel; Speck, James S.; Nakamura, Shuji; DenBaars, Steven P.
Abstract: We demonstrate removal of homoepitaxially grown semi-polar gallium nitride (GaN) layers from the native substrates. The weak link at the interface of the epitaxial lateral overgrowth and cleavable m -plane of the respective native semi-polar plane is used to separate homoepitaxial GaN from its native substrate. Homoepitaxial GaN layers of the semi-polar planes, (10 1 ̄ 1), (20 2 ̄ 1), (30 3 ̄ 1), (10 1 ̄ 1 ̄ ), (20 2 ̄ 1 ̄ ), and (30 3 ̄ 1 ̄ ) are successfully removed. This approach allows the reuse of expensive semi-polar GaN substrates, eliminating one barrier to market introduction of superior optoelectronic devices grown with semi-polar orientations.